Cohort Trends in the Gender Distribution of Household Tasks in the United States and the Implications for Understanding Disability. (December 2019) - Sheehan, Connor; Domingue, Benjamin W.; Crimmins, Eileen
Objectives: Measures of disability depend on health and social roles in a given environment. Yet, social roles can change over time as they have by gender. We document how engagement in Instrumental Activities of Daily Living (IADLs) is shifting by gender and birth cohort among older adults, and the challenges these shifts can create for population-level estimates of disability.Method: We used the Health and Retirement Study ( N = 25, 047) and multinomial logistic regression models with an interaction term between gender and birth cohort to predict limitation and nonperformance relative to no difficulty conducting IADLs.Results: Nonperformance of IADLs have significantly decreased among younger cohorts. Women in younger cohorts were more likely to use a map, whereas men in younger cohorts were more likely to prepare meals and shop.Discussion: Failing to account for gender and cohort changes in IADL, performance may lead to systematic bias in estimates of population-level disability.